2008
DOI: 10.1007/s11832-007-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Local and distant effects of isolated calf muscle lengthening in children with cerebral palsy and equinus gait

Abstract: Purpose The purpose was to assess the local and distant effects of isolated calf muscle lengthening in ambulant children with cerebral palsy. Methods The study included fifteen ambulant children with cerebral palsy (nine with diplegia and six with hemiplegia), average age 8.8 years, Gross Motor Function Classification System (GMFCS) level I and II. None of the children had previously undergone orthopaedic surgery, apart from one child who had tendo-achilles lengthening (TAL) nine years earlier. All the childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 14 publications
1
55
0
6
Order By: Relevance
“…Calcaneus deformity, calcaneus gait and crouch gait by topographical distribution Nine of the 35 studies reported explicit criteria for calcaneal gait, calcaneal deformity or crouch gait [2,17,19,20,22,27,38,39,44]. These definitions included the inability to passively plantarflex the foot to neutral, greater than 14°T of ankle dorsiflexion in stance or 10°of ankle dorsiflexion greater than the normal, as a definition of calcaneus deformity and the need for a floor reaction orthosis for crouch gait.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…Calcaneus deformity, calcaneus gait and crouch gait by topographical distribution Nine of the 35 studies reported explicit criteria for calcaneal gait, calcaneal deformity or crouch gait [2,17,19,20,22,27,38,39,44]. These definitions included the inability to passively plantarflex the foot to neutral, greater than 14°T of ankle dorsiflexion in stance or 10°of ankle dorsiflexion greater than the normal, as a definition of calcaneus deformity and the need for a floor reaction orthosis for crouch gait.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…oraz Chang'a II Park'a i wsp. po twier dzi ły po pra wę ki ne ty ki oraz ki ne ma tyki sta wu sko ko we go po wy ko na niu wy dłu że nia ścię -gna Achil le sa [16,17]. Brak na to miast w opu bli ko wanych ba da niach pró by wy ja śnie nia przy czy ny stop niowe go na ra sta nia wraz z wie kiem ilo ści na wro tów u pa cjen tów ope ro wa nych po 8 ro ku ży cia.…”
Section: Discussionunclassified
“…To enable a more accurate determination of the risk of recurrence, the patients were divided into two groups according to whether they had been operated before or after reaching the age of 8 years. Group I, those operated before the age of 8 years, ni okres ob ser wa cji w gru pie I wy niósł 9,77 lat (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), na to miast w gru pie II śred ni okres ob ser wa cji wy niósł 10,76 lat (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies on foot deformities in children with CP focused on local and more proximal effects of isolated surgical correction of equinus foot deformity [9][10][11][12]. The results of these studies showed that, although after correcting an equinus deformity ankle kinematics were significantly improved, the surgical correction had a smaller and more variable effect on more proximal joints like the knee.…”
Section: Introductionmentioning
confidence: 99%